Exploration of the value of progesterone and progesterone/estradiol ratio on the hCG trigger day in predicting pregnancy outcomes of PCOS patients undergoing IVF/ICSI: a retrospective cohort study - Yiqing Yang; Bowen Liu; Gengxiang Wu; Jing Yang (BMC, 2021)
Abstract Background Polycystic ovary syndrome (PCOS) is a common endocrine disorder with the disorders of estrogen(E2) and progesterone(P) secretion. The purpose of this study was to evaluate the association between the progesterone level or progesterone/estradiol(P/E2) ratio on human chorionic gonadotropin (hCG) trigger day and the outcome of in vitro fertilization in PCOS patients and explore the value of progesterone and P/E2 ratio for predicting the clinical pregnancy. Methods The clinical data of 1254 PCOS patients who satisfied the inclusion criteria were retrospectively analyzed, including baseline characteristics such as age, body mass index, basal sex hormone levels, et al., as well as ovarian stimulation data and clinic outcome. Results The number of follicles larger than 14 mm in diameter (P < 0.001) and retrieved oocytes (P < 0.001) was greater in the high progesterone group (progesterone ≥ 0.92 ng/mL). In the high P/E2 group(P/E2 ratio ≥ 0.3), the number of follicles larger than 14 mm in diameter (P < 0.001) and retrieved oocytes (P < 0.001), as well as the rate of high-quality embryos (P = 0.040) were significantly decreased. In ultralong GnRH agonist protocol, the implantation rate(P < 0.001), hCG positive rate (P < 0.001), clinical pregnancy rate (P < 0.001) and live birth rate (P < 0.001) were all significantly higher than long GnRH agonist protocol and GnRH antagonist protocol. The clinical pregnancy rate of high progesterone group was significantly lower than that of low progesterone group in ultralong GnRH agonist (P = 0.008). The progesterone level could be used as an indicator to predict the positive clinical pregnancy (long GnRH agonist: P = 0.001; ultralong GnRH agonist: P < 0.001) except in cycles using GnRH antagonist (P = 0.169). In the ultralong GnRH agonist, the value of progesterone level in the prediction of clinical pregnancy was significantly higher than that of the P/E2 ratio (P = 0.021). Conclusions In PCOS patients, the progesterone level is associated with clinical pregnancy rate while P/E2 ratio is not. In subgroup analysis using three different COS protocols, a significant association between progesterone level and clinical pregnancy rate can be observed in the long GnRH agonist protocol and ultralong GnRH agonist protocol. The progesterone level is significantly better than the P/E2 ratio in predicting the pregnancy outcome of PCOS patients, especially in ultralong GnRH agonist cycles.